PREDIKSI JUMLAH PENGANGGURAN DI INDONESIA BERDASARKAN DATA TIME SERIES MENGGUNAKAN REGRESI LINEAR - Apredo Suranta Singarimbun; Dede Brahma Arianto (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Unemployment is a very big problem. The purpose of this research is to predict the number of unemployed people based on the working-age population. To produce an accurate prediction, valid data and a long period of time are needed. This is a reference for forecasting the unemployment population based on the last 5 years. To do forecasting, a method is needed, namely the Linear Regression method. Linear regression is a statistical method that serves to test how far the relationship between the cause variable and the effect variable is. After forecasting, prediction data is obtained in 2025. Where the number of working-age population in 2025 is predicted to be 218.21 million people and the number of unemployed people is 6.77 million people.